2002
DOI: 10.1139/w02-095
|View full text |Cite
|
Sign up to set email alerts
|

Soil and plant effects on microbial community structure

Abstract: We investigated the effects of two different plant species (corn and soybean) and three different soil types on microbial community structure in the rhizosphere. Our working hypothesis was that the rhizosphere effect would be strongest on fast-growing aerobic heterotrophs, while there would be little or no rhizosphere effect on oligotrophic and other slow-growing microorganisms. Culturable bacteria and fungi had larger population densities in the rhizosphere than in bulk soil. Communities were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(111 citation statements)
references
References 26 publications
14
94
1
2
Order By: Relevance
“…Nunan et al [21] observed that topography and other uncharacterized factors were important in driving changes in the composition of bacterial communities in grassland soils. And similar to what we found, Buyer et al [1] observed a very strong soil effect but little plant effect between corn and soybean rhizosphere communities by fatty acid analysis, indicating that the overall microbial community structure was not affected by these particular rhizospheres. The difference in these results is difficult to explain due to differences in the experimental conditions, methodologies, plant species, etc.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nunan et al [21] observed that topography and other uncharacterized factors were important in driving changes in the composition of bacterial communities in grassland soils. And similar to what we found, Buyer et al [1] observed a very strong soil effect but little plant effect between corn and soybean rhizosphere communities by fatty acid analysis, indicating that the overall microbial community structure was not affected by these particular rhizospheres. The difference in these results is difficult to explain due to differences in the experimental conditions, methodologies, plant species, etc.…”
Section: Discussionsupporting
confidence: 91%
“…Several variables are correlated to this effect such as plant species, land management (e.g., application of herbicides and fertilizers), changes in soil physical and chemical attributes, etc. [1,8,10,17,18,20]. Differences in the composition of microbial communities are also linked to factors independent of the agricultural activity, such as soil type and geographic distance.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis from DGGE profiles in the Biolog wells indicated that different subsets of rhizosphere communities became dominant after incubation. This finding could be partially attributed to the fact that culturable bacteria are 'r-strategists' , and they respond very quickly to the changes in types of exudates in the rhizosphere compared with the oligotrophic species (K-strategists) in the wells (Buyer et al 2002). In conclusion, the two soybean genotypes induced distinct rhizosphere microbial communities.…”
Section: Discussionmentioning
confidence: 90%
“…Microbial communities seem to be weakly related to the studied successional gradient of vegetation in terms of functional structure and indeed, for chalk grassland Chabrerie et al (2003) came to the conclusion of independency. In some cases, microbial community structure (PLFA) and activity (Biologä) are more influenced by the soil type than by the plants (Buyer et al, 2002).…”
Section: Relationship Between Microbial Communities and Light Conditionsmentioning
confidence: 99%